2009
DOI: 10.1021/om900916g
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)-Catalyzed Intermolecular Benzylic C−H Amination with 2,2,2-Trichloroethoxycarbonyl Azide (TrocN3)

Abstract: 2,2,2-Trichloroethoxycarbonyl azide (TrocN 3 ) is an effective nitrene source for cobalt(II)-catalyzed intermolecular nitrene insertion of C-H bonds. Among different metalloporphyrins studied, Co(II)-(TPP) was shown to be a competent catalyst for the selective amination of various benzylic C-H bonds under mild conditions without the need of other reagents or additives, forming the desired Trocprotected amines in moderate to high yields with nitrogen gas as the only byproduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…4 Given the ubiquity of nitrogen atoms in biologically active compounds, 8 nitrene transfer reactions also have very important applications in making molecules of interest. However, the applicability of metal-nitrenoids has so far been limited to alkene aziridination, 9,10 C–H amination 11,12 and amidation. 13 …”
Section: Introductionmentioning
confidence: 99%
“…4 Given the ubiquity of nitrogen atoms in biologically active compounds, 8 nitrene transfer reactions also have very important applications in making molecules of interest. However, the applicability of metal-nitrenoids has so far been limited to alkene aziridination, 9,10 C–H amination 11,12 and amidation. 13 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, efficient models of myoglobin Mb [1] and cytochrome c oxidase CcO [2] have been described. For enantioselective reactions such as epoxidation [3], cyclopropanation [4], aziridination [5], amination [6] and functionalization of non-activated C-H bonds [7], prodigious effort has been devoted to obtain catalysts using the rigid core of a porphyrin and judicious functionalization of the periphery of the macrocycle [8]. In this context, binaphthyl porphyrins have appeared to be interesting chiral porphyrins [9] since the pioneering work of Groves et al in 1983 [10], who first reported the synthesis of 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The solvent was then removed under vacuum, and the dark purple residue purified by chromatography column on silica gel (SiO 2 15 µm, eluent dichloromethane/ methanol: 99/1) to afford the bis-strapped porphyrin as a red-purple solid (318 mg, 87%). 1 H NMR (500 MHz, CDCl 3 , 293 K): δ H , ppm -2.06 (2H, br s, NH pyr ), 0.15 (12H, s, OMe), 6.00 (4H, dd, 3 J = 8.6 Hz, 4 J = 0.7 Hz, H 8′ ), 6.85 (4H, ddd, 3 J = 8.5 Hz, 3 J = 6.7 Hz, 4 J = 1.2 Hz, H 7′ ), 7.12 (4H, ddd, 3 J = 8.3 Hz, 3 J = 6.7 Hz, 4 J = 0.9 Hz, H 6′ ), 7 13 C NMR (125 MHz, CDCl 3 , 293K): δ C , ppm 58.4 (OMe), 113.6 (C meso ), 122.8 (C 1′ ), 123.7 (C 3 ), 123.9 (C 5 ), 124.4 (C 8′ ), 124.5 (C 3′ ), 125.6 (C 6′ ), 128.4 (C 7′ ), 129.17 (C 5′ ), 129.19 (C 4′a ), 130.0 (C 4 ), 131.6 (C β ), 131.9 (C 1 ), 132.4 (C β ), 132.7 (C 6 ), 134.3 (C 4′ ), 135.0 (C 8′a ), 139.5 (C 2 ), 151.3 (C 2′ ), 163.0 (C CO Synthesis of αβαβC 2 basket handle porphyrin. A 250 mL two-neck round-bottom flask equipped with a rubber and an argon inlet is charged with 150 mL of freshly distilled tetrahydrofuran on sodium.…”
mentioning
confidence: 99%
“…[4] As stable metalloradicals, cobalt(II) complexes of porphyrins, [Co(Por)], have emerged as a new class of catalysts for CÀH amination. [6] The cobalt(II)-based metalloradical amination (MRAm) is different from the commonly studied Rh 2 system, as it can operate effectively with various azide substrates without the need for terminal oxidants and other additives. [7][8][9][10][11] To further validate the utility of C À H amination methodology based on a cobalt(II) catalyst and azides, we envisioned a general strategy for the synthesis of 1,3-diamines from monoamines through the key step of the intramolecular C À H amination of sulfamoyl azides with [Co(Por)] (Scheme 1).…”
mentioning
confidence: 99%